Nossos corpos não são mais os mesmos : narrativas de mulheres trans e travestis sobre o processo de envelhecimento - Lima, Ana Paola de Souza (2019)
ABSTRACT The experiences of trans women and transvestites trigger a series of analysis about the gender binarism male/female, since their materialization occurs through the construction of an image which distorts the image of femininity imposed by the hetero-cis-normative discourse. Moreover, the age-old generational category, likewise inserts itself in a field undermined by discourses guided by other binarisms as healthy/harmful; worthy/unworthy; right/wrong; beautiful/ugly, youth/elderly. This doctoral research, therefore, aims to analyze narratives about the aging process of trans women and transvestites, with the objectives of: a) understand how travestites/trans women construct meanings about themselves, whether they are elderly or not; b) understand how travestites/trans women perceive/signify their aging process; c) assimilate how travestites/trans women articulate the notions of gender and aging in their identity construction. The questions that guided this study were: 1. How do travestites/trans women mean their aging process? and, 2. In what ways do the violence suffered by travestites/trans women, in their trajectories, determine the markers of the onset of their aging process? For that, I used qualitative-interpretative research (FLICK, 2009, KING; HORROCKS, 2010; DENZIN; LINCOLN, 2006) since it does not constitute another binarism - right / wrong, but it supports in a given context from the lens of a given researcher. The narrative interview was the main tool, organized as open questions. The results show the aging process of trans women and travestities is not based on a chronological age, and also, it suffers influence of a variety of manners of violence faced by them.